IMPLEMENTATION OF 2015 MENTORING PROGRAM IN ENGLISH DEPARTMENT OF UNIVERSITY MUHAMMADIYAH MALANG - Nina Inayati; Laela Hikmah Nurbatra; Rahmawati Khadijah Maro (University of Muhammadiyah Malang, 2017)
ABSTRACT The Mentoring Program of the English Department of UMM is an extra-curricular program designed to assist first year students to practice their English speaking and independent study. The speaking skills are focused on two specific skills; presentation and debate skills; while the English independent study introduces students to various English learning activities students could potentially integrate in their daily lives. The current study employs document analysis and survey as the methods of data collection. Then, content analysis is used to identify the salient themes and patterns occurring from the data to be presented based on the research problems. Analysis of the data shows that the program ran as planned and that some mentors developed the prepared lesson plans. As for the program evaluation, analysis of the survey results show that, in general, the program was viewed positively by the students. Some strengths mentioned were that the module was helpful and informative and that the mentors were fun and motivating. As for the weaknesses, Saturday morning schedule was considered bad option and that outdoor venues were less conducive some times. In light of the evaluation, some suggestions for the future program are offered, such as to improve the timing and venues. Keywords: Mentoring, English Learning, Speaking, Independent Study